De José Benito a Dom Agostinho: um religioso entre conflitos, negociações e tensões sociais no Paraná - Santos, Jael dos (2019)
This work objective is the objective of this work is to problematize, from a biographical approach, the sociocultural, ecclesial and political trajectory of Dom Agostinho José Sartori. Baptized José Benito Sartori and of Italian ancestry, he was born in 1929. He entered the seminary of the Order of Friars Less Capuchins at the age of 9 in 1939. He was ordained a priest in 1952. After 18 years, this character was, between the years of 1970 and 2005 , Bishop of the current Diocese of Palmas / Francisco Beltrão-PR. In view of the many positions of subject that he assumed - descendant of immigrants, Capuchin seminarian, priest and bishop -, the premise is that the historicity of this historical character provides vectors of understanding and complexity both on the social tensions that marked the Southwest region of Paraná in the period and as to how the Catholic Church became present before the different realities present in Brazil. Thinking about the processes that defined the Catholic Church in the last one hundread and fifty years, both in the world and in Brazil, Archbishop Augustine is a religious who has traveled through universes of signification and resignification that are extremely tense and crucial to the history of the Church - of Romanization to the results of the Second Vatican Council; of the socio-political amalgamation between Church and State in Brazil until the crisis experienced between these institutions during the Civil-Military Dictatorship. In this sense, another fundamental point of the research is to analyze to what extent Don Agostinho's pastoral proposals were tributary or not to his formation and expression of the expectations and tensions that he was experiencing during his personal trajectory. It is in the problematizing of these aspects that the political readings of the main character of this research will be thought, which made him come closer and move away from important movements and character of the history of the Brazilian and Paranaian Church in the XX century. Augustine, as it will be shown, was as contradictory a character as the Catholic Church itself in the period, while at the same time compromising the Tradition of the Institution, it also showed, although timidly, concordances with more interventionist perspectives of action in face of social problems the period. Specifically, in the case of pastoral action within and outside the Southwest region of Paraná, the local diocesan fragmentation, the state agrarian problem, the rural exodus produced by this process, the disorderly formation of the cities and the construction of a fundamentally diocesan structure.